A meta-analysis of telemedicine success in Africa - Dan S Wamala; Kaddu Augustine (Elsevier, 2013)
The use of information and communication technologies (ICT) tools to improve the efficiency of professionalism at work is increasing every time under the dynamic digital environment. Tools such as telemedicine, tele-education, and health informatics have of late been incorporated in the health sector to enable easy access to essential services, for example, in medical areas from referral centers by the patients on one hand and enabling the doctor to doctor consultations for the benefit of patients. Unfortunately, observations indicate dearth efforts and commitment to optimize use of the tools in the majority of the countries south of the Sahara. Sub-Saharan Africa has been left almost behind the rest of the world in terms of development going through decades of economic exploitation by especially the west through its natural and human resources. These factors, ethnic conflicts and endless wars have continued to ruin sub-Saharan Africa's socio-economic development. Information was obtained through a network of telemedicine practitioners in different African countries using internet communication, through E-mail and reviewing existing literature of their activities. This information was compiled from representative countries in each African region and the previous authors'experiences as telemedicine practioners. Most of these countries have inadequate ICT infrastructure, which yet creates sub-optimal application. Sub-Saharan Africa, made up of 33 of the 48 global poorest countries has to extend its ICT diffusion and policy to match the ever developing global economy. In some countries such as Ethiopia and South Africa there is significant progress in Telemedicine while in countries such as Burkina Faso and Nigeria the progress is slow because of lack of political support. Almost all reference to Africa is made in due respect to sub-Saharan Africa, one with big social, economic, and political problems with resultant high morbidity and mortality rates. This also highlights the under-representation of African researchers in the global whelm of information system research. Telemedicine in Africa though has not attracted enough political support is potentially a very useful conduit of health-care given the fact that the continent is resource limited and still enduring the effects of scarce human resource especially in health.